Cienfuegos Medical Sciences Faculty contribution to the use of computer technology in higher medical teaching. Review of the clinical simulations use from 1990 to 2007 - Luis Alberto Corona Martínez; Mercedes Fonseca Hernández (Medisur)
The objective of this article is to review chronologically, the most relevant events related to the use of computerized simulations in the teaching process, in the particular context of the Cienfuegos Medical Sciences Faculty from 1990 to 2007. Among the identified events are: the development and introduction of simulations in the Internal Medicine subject corresponding to the third year of the degree (course 1990-1991); the introduction of simulation, for evaluation purposes, in the Internal Medicine internship (1997-2000); the development of a new software for the elaboration of simulations (2002); and the extension of the use of simulations to therapeutic update seminars corresponding to the Pediatrics internship (2007). It was evidenced that the contribution made by the educational institution to the topic addressed, not only consisted in the preparation of simulation exercises and their introduction in the training practice, but also in the teacher training, the improvement of the tools used (programs, methodologies) and the sharing of experiences; all of which was accompanied by extensive research activity that deserved recognition at different levels.